The impacts of democratic classroom on students’ personal growth - Hamzah, Lina Mursyidah (Department of Social Science , Nandurburg, 2020)
This qualitative study examines the impact of democratic classroom on students’ self-growth. By choosing case study as the research design, the interview was conducted on six participants who have experienced the democratic classroom approach in their teaching and learning. Data from the interviews had been analysed using the thematic analysis. There are two major themes that had been drawn from the interview of the participants. The findings of the study show that when students were having the democratic classroom approach in their teaching and learning, they felt appreciated, and their confidence level and sense of belonging were enhanced. Therefore, the study suggests that educators need to know how to develop students’ self-growth, which also indicates the betterment of students’ well-being during the teaching and learning process